2019
DOI: 10.1117/1.oe.58.9.092604
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface mechanical damage correlations after grinding of various optical materials

Abstract: Loose abrasive grinding was performed on a wide range of optical workpiece materials [single crystals of Al 2 O 3 (sapphire), SiC, Y 3 Al 5 O 12 (YAG), CaF 2 , and LiB 3 O 5 (LBO); a SiO 2 -Al 2 O 3 -P 2 O 5 -Li 2 O glass-ceramic (Zerodur); and glasses of SiO 2 ∶TiO 2 (ULE), SiO 2 (fused silica), and P 2 O 5 -Al 2 O 3 -K 2 O-BaO (phosphate)]. Using the magneto rheological finishing (MRF) taper wedge technique (where a wedge was polished on each of the ground workpieces and the resulting samples were appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…First, this correlation suggests simple static indentation parameters can be effectively used to model and draw conclusions regarding more complex, dynamic processes involving sliding indentation such as grinding processes. In fact, this explains why previous grinding models utilizing static indentation behavior appear to do a reasonable job at predicting grinding behavior . Second, since it has been previously shown that lateral crack depth during static indentation scales as E 1 1/2 / H 1 of the workpiece material, this implies a similar scaling would apply for sliding indentation and hence grinding processes.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…First, this correlation suggests simple static indentation parameters can be effectively used to model and draw conclusions regarding more complex, dynamic processes involving sliding indentation such as grinding processes. In fact, this explains why previous grinding models utilizing static indentation behavior appear to do a reasonable job at predicting grinding behavior . Second, since it has been previously shown that lateral crack depth during static indentation scales as E 1 1/2 / H 1 of the workpiece material, this implies a similar scaling would apply for sliding indentation and hence grinding processes.…”
Section: Discussionmentioning
confidence: 80%
“…As discussed in the Introduction, various grinding characteristics (such as material removal rate, surface roughness, and sub‐surface mechanical damage) during optical fabrication have been shown to correlate with the characteristics and propensity of lateral cracks. Previous grinding models have quantitatively utilized the lateral crack material and load correlations (as measured by static Vickers indentation) with good success . The results shown in Figure , which illustrates that static and sliding indentation lateral crack depth behavior are directly correlated, have some important implications with respect to understanding and predicting grinding processes.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations